Klinická pastoracní péce a její poskytovatel - Opatrná, M (Casopis lekaru ceskych, 2006)
Paper is aimed at the role of pastoral workers within the activity of multidisciplinary teams.
Keywords: Pastoral Care; týmová péče o pacienty; pastorační péče; lidé; Patient Care Team; Humans